Orthogonal latent space learning with feature weighting and graph learning for multimodal Alzheimer’s disease diagnosis - Chen, Zhi; Liu, Yongguo; Zhang, Yun; Li, Qiaoqin (Medical image analysis, 2023)
Recent studies have shown that multimodal neuroimaging data provide complementary information of the brain and latent space-based methods have achieved promising results in fusing multimodal data for Alzheimer’s disease (AD) diagnosis. However, most existing methods treat all features equally and adopt nonorthogonal projections to learn the latent space, which cannot retain enough discriminative information in the latent space. Besides, they usually preserve the relationships among subjects in the latent space based on the similarity graph constructed on original features for performance boosting. However, the noises and redundant features significantly corrupt the graph. To address these limitations, we propose an Orthogonal Latent space learning with Feature weighting and Graph learning (OLFG) model for multimodal AD diagnosis. Specifically, we map multiple modalities into a common latent space by orthogonal constrained projection to capture the discriminative information for AD diagnosis. Then, a feature weighting matrix is utilized to sort the importance of features in AD diagnosis adaptively. Besides, we devise a regularization term with learned graph to preserve the local structure of the data in the latent space and integrate the graph construction into the learning processing for accurately encoding the relationships among samples. Instead of constructing a similarity graph for each modality, we learn a joint graph for multiple modalities to capture the correlations among modalities. Finally, the representations in the latent space are projected into the target space to perform AD diagnosis. An alternating optimization algorithm with proved convergence is developed to solve the optimization objective. Extensive experimental results show the effectiveness of the proposed method. [Display omitted] •A method named OLFG is presented for fusing neuroimaging data for AD diagnosis.•We combine space learning, graph learning and classifier training into a framework.•We introduce feature weighting and orthogonal projection for space learning.•We explore the correlations among modalities by an adaptive joint graph.•Results on ADNI dataset show the effectiveness of our model.